Lysosomal Storage Disorders Shed Light on Lysosomal Dysfunction in Parkinson’s Disease - Blumenreich, Shani (Int J Mol Sci, 2020)
The lysosome is a central player in the cell, acting as a clearing house for macromolecular degradation, but also plays a critical role in a variety of additional metabolic and regulatory processes. The lysosome has recently attracted the attention of neurobiologists and neurologists since a number of neurological diseases involve a lysosomal component. Among these is Parkinson’s disease (PD). While heterozygous and homozygous mutations in GBA1 are the highest genetic risk factor for PD, studies performed over the past decade have suggested that lysosomal loss of function is likely involved in PD pathology, since a significant percent of PD patients have a mutation in one or more genes that cause a lysosomal storage disease (LSD). Although the mechanistic connection between the lysosome and PD remains somewhat enigmatic, significant evidence is accumulating that lysosomal dysfunction plays a central role in PD pathophysiology. Thus, lysosomal dysfunction, resulting from mutations in lysosomal genes, may enhance the accumulation of α-synuclein in the brain, which may result in the earlier development of PD.